Co-encapsulation of chlorogenic acid and cinnamaldehyde essential oil in Pickering emulsion stablized by chitosan nanoparticles - Ben Niu (Food Chemistry: X, 2022)
Most of the current research only explored the loading of an active substance in active packaging. In this study, cinnamaldehyde essential oil (CEO) and chlorogenic acid (CA) were co-encapsulated in chitosan (CS) nanoparticles based Pickering emulsion. The morphology and wettability of CS-CA particles were determined. In addition, physicochemical characterizations and stability of the Pickering emulsion were also investigated. Results showed that the wettability of nanoparticles was improved with increasing the ratios of CS to CA, which is helpful to stabilize the emulsion. CEO Pickering emulsion was stabilized by CS-CA nanoparticles and CEO emulsion showed the best stability by using CS-CA nanoparticles with the ratios of CS to CA 1:0.75 with the minimum creaming index value of 26.5 ± 4.6% after 5 days of storage. These overall results presented in this work demonstrate, for the first time, the potential of Pickering emulsion for the co-encapsulation of water-soluble and water-insoluble ingredients.